2004
DOI: 10.1016/j.jcrs.2003.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Comparative clinical trial of topical anesthetic agents in cataract surgery

Abstract: Lidocaine gel was a better topical anesthetic agent than bupivacaine and benoxinate drops. Bupivacaine drops were effective in providing deep topical anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 20 publications
4
11
0
Order By: Relevance
“…Bupivacaine 0.5% eyedrops alone did not provide satisfactory topical anesthesia [unpubl. observation], and others have shown that bupivacaine alone seems to be in fact less effective than lidocaine gel [10]. In order to provide better anesthesia and possibly analgesia, a combination of bupivacaine 0.5%, oxybuprocaine 1% and diclofenac eyedrops was used, and the eyedrops combination was administered 4 times prior to cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Bupivacaine 0.5% eyedrops alone did not provide satisfactory topical anesthesia [unpubl. observation], and others have shown that bupivacaine alone seems to be in fact less effective than lidocaine gel [10]. In order to provide better anesthesia and possibly analgesia, a combination of bupivacaine 0.5%, oxybuprocaine 1% and diclofenac eyedrops was used, and the eyedrops combination was administered 4 times prior to cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The safety and utility of the jelly formulation has been studied and demonstrated in several studies. [14] Jelly provides comparable[1516] and possibly superior anesthesia,[1718] wets the corneal surface, aids in pupillary dilatation without the use of sympathomimetics or parasympatholytic agents. [14] Adding intracameral lignocaine solution aids in increasing patient comfort and is safe and assists in pupillary dilatation.…”
Section: Methodsmentioning
confidence: 99%
“…Soliman et al reported that 73.3% of patients that received topical 0.4% benoxinate and 10% of patients that received topical 0.5% bupivacaine during phacoemulsification surgery had severe to unbearable pain which led to addition of subtenon lidocaine injection [4]. In our study, seven patients (14.2%) experienced severe to unbearable pain which necessitated intracameral lidocaine injection.…”
Section: Discussionmentioning
confidence: 60%
“…The three most common methods of applying topical anesthesia are by eye drops, by eye drops with intracameral lidocaine injection, and in gel form [3, 4]. Topical anesthesia by eye drops is a noninvasive method, but in some cases it may provide insufficient analgesia and require an additional intracameral lidocaine injection [5].…”
Section: Introductionmentioning
confidence: 99%